Solução da equação do telégrafo pelo método das características usando uma maplet - Lobeiro, Adilandri Mércio (2013)
This paper presents a Maplet, programmed via Maple, designed for the numerical solution of a Partial Differential Equation known as the Telegraph Equation by the Method of Characteristics. This work initially addresses basic notions of Partial Differential Equations and proceeds with the presentation of the model of an Electrical Circuit expressed mathematically by means of these equations, working with the concepts needed to understand this physical phenomenon, describing step by step procedures that were implemented to obtain the solution through Method of Characteristics. Finally, the functionality of the Maplet developed on theoretical reasoning is exposed and the numerical solution of a particular example of the Telegraph Equation is presented with the aid of the Maple graphical interface.